2021
DOI: 10.1073/pnas.2015102118
|View full text |Cite
|
Sign up to set email alerts
|

Neural divergence and hybrid disruption between ecologically isolatedHeliconiusbutterflies

Abstract: The importance of behavioral evolution during speciation is well established, but we know little about how this is manifest in sensory and neural systems. A handful of studies have linked specific neural changes to divergence in host or mate preferences associated with speciation. However, the degree to which brains are adapted to local environmental conditions, and whether this contributes to reproductive isolation between close relatives that have diverged in ecology, remains unknown. Here, we examine diverg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 116 publications
7
50
1
Order By: Relevance
“…As we made sure to only include sites so that urban–rural distances were short (10 to 40 km), our evidence for differences appears remarkable, especially for P. napi given its considerably higher mobility, and hence higher gene flow, than C. clathrata ( 42 , 50 ). However, heritable divergence in the face of ongoing gene flow is achievable when a strong selection pressure leads to divergent selection and local adaptation to distinct selective optima, and indeed, divergence between populations in the face of gene flow is considered strong evidence for local adaptation ( 51 , 52 ). Since the diapause trait is essential for winter survival in temperate and boreal insects, it is under strong selection, which could counteract such gene flow ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…As we made sure to only include sites so that urban–rural distances were short (10 to 40 km), our evidence for differences appears remarkable, especially for P. napi given its considerably higher mobility, and hence higher gene flow, than C. clathrata ( 42 , 50 ). However, heritable divergence in the face of ongoing gene flow is achievable when a strong selection pressure leads to divergent selection and local adaptation to distinct selective optima, and indeed, divergence between populations in the face of gene flow is considered strong evidence for local adaptation ( 51 , 52 ). Since the diapause trait is essential for winter survival in temperate and boreal insects, it is under strong selection, which could counteract such gene flow ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other examples [39,40,49], the effects we see here act across very short time and spatial scales, reflecting the fluctuating sensory conditions experienced by our study species in their rainforest environments. By contrast to more divergent Heliconius species pairs [50,51], H. heurippa and H. t. linaresi are not known to differ in ecology or habitat type, and there is little reason to suspect that differences in their sensory environment drive divergence in mating preferences, or sensory behaviours more broadly. Instead, differences in female wing pattern (driven by local selection for aposematism) likely impose divergent sexual selection on male preferences to improve their ability to find receptive females [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining how the brain evolves have largely been restricted to comparative studies between closely related, albeit different species, and these studies have revealed gross differences in neuroanatomy, connectivity, and function between derived animals (5, 9, 10, 12, 14). However, the Astyanax model provides a powerful tool for assessing how the brain evolves in a single species with multiple divergent forms and an extant ancestor (20, 22, 37).…”
Section: Discussionmentioning
confidence: 99%